Evaluation of low-copy nuclear genes SQD1 and pgiC as DNA barcodes for Stenochlaena palustris - Dwiyanti, Maria Stefanie (Agriculture and Natural Resources, 2022)
Importance of the work: Identifying potential low-copy nuclear genes as DNA barcodes is needed because there is little genetic information on Stenochlaena palustris. Objectives: To sequence the nuclear genes SQD1 and pgiC and to evaluate their suitability as DNA barcodes for S. palustris. Materials & Methods: SQD1 and pgiC were amplified using the DNA of 19 S. palustris samples collected from five locations in Central Kalimantan, Indonesia. The polymerase chain reaction (PCR) products were sequenced using direct Sanger sequencing methods and the chromatograms were examined. The resulting nucleotides were compared within S. palustris and with the known SQD1 and pgiC sequences of other ferns. Results: Direct sequencing showed that SQD1 was present as a single copy and the nucleotide sequence was highly conserved among S. palustris samples. It also showed nucleotide variations compared with SQD1 from other ferns. On the other hand, pgiC produced a single copy of sequence in seven samples but multiple PCR products in the remaining samples. Based on results of the seven samples, pgiC was conserved within S. palustris. Nucleotide variations were observed between pgiC from S. palustris and that from other Blechnaceae ferns. Main finding: This was the first report on the SQD1 and pgiC sequence of S. palustris. The availability of both sequences will support species identification of S. palustris, in addition to using chloroplast genes.